The Implementation of Green Marketing Tools in Rural Tourism: The Readiness of Tourists? - Chin, Chee-Hua; Chin, Chee-Ling; Wong, Winnie Poh Ming (Routledge, 2017)
Environmental sustainability is the key factor for the future development of the tourism industry, particularly in sensitive rural tourism destinations. Green tourism and green marketing are alternative practices that ensure the environmental sustainability of tourism destinations. However, green marketing has received little attention in the context of rural destinations. This is the first known study undertaken with the purpose of understanding the relationship between green marketing tools (eco-brand, eco-label, and environmental advertisement) and green purchasing behavior in rural tourism destinations from the perception of tourists. A sample of 252 respondents was selected to complete the questionnaires. To assess the developed model, SmartPLS (version 3.2.6) was applied based on path modeling, followed by bootstrapping. The results revealed that the three-dimensional constructs of green marketing tools were significantly and positively correlated with green purchasing behavior of rural tourism destinations from tourists’ perspectives. Several implications, limitations, and directions for future research were further discussed. © 2017 Taylor & Francis Group, LLC